Description of fourty four new species, taxonomic notes and identification key to Neotropical Trichomyia Haliday in Curtis (Diptera: Psychodidae, Trichomyiinae) - Araújo, Maíra Xavier; Bravo, Freddy (Zootaxa, 2016)
Trichomyia Haliday in Curtis is distributed worldwide, except in Antarctica. The Neotropical region has the greatest known species richness of Trichomyia, with 76 described species, compared with five in the Nearctic region, nine in the Palearctic, five in the Afrotropical region, six in the Oriental region, and 46 in the Australasian region. Two morphological groups within the genus have been previously recognized: Group A, comprising species with four clearly differentiated palpus segments; and Group B, comprising species with three palpus segments, as well as a group of species with four palpus segments but with the two basal segments not fully articulated (partially fused). We examined 1,330 specimens of Trichomyia that were collected almost exclusively from Brazil, specifically from the states of Amazonas, Pará, Bahia, Roraima, Rondônia, and Minas Gerais. 44 new species have been identified, representing an increase of 37% for this genus in the Neotropical region. In order to facilitate their study, some species are placed in provisional morphological groups. The distributions of five species of Trichomyia are expanded and a key to the males of Neotropical species is presented.